The impact of design factors of virtual and augmented reality on tertiary students’ user experience in Metaverse - Julius G. Garcia; Alvie Simonette Q. Alip (International Journal of Evaluation and Research in Education (IJERE), 2026)
The Metaverse is a convergent space integrating virtual reality (VR) and augmented reality (AR) technologies, with market projections rising from $65.5 billion in 2022 to $1.3 trillion by 2030. Despite rapid adoption in education, the specific contributions of visual elements, environmental design, and communication features to user experience (UX) remain underexplored, limiting evidence-based design and resource allocation. This study examined how these design factors in VR and AR environments influence UX in Metaverse platforms. Using a correlational research design, data were collected from 321 purposively sampled tertiary students from engineering and computer science departments across four higher education institutions, all familiar with Metaverse platforms. A structured questionnaire with validated 5-point Likert scales measured UX; visual elements (field of view, resolution, color, complexity, and style); environmental design (interactivity, cohesiveness, naturalness, and complexity); and communication features (text/audio/video tools, avatar interaction, and spatial audio). Multiple regression analysis assessed the independent and combined effects of these factors on UX. Results show that environmental design (β=0.424, p<0.001) and visual elements (β=0.298, p<0.001) are the primary predictors of UX, jointly explaining 47.3% of its variance, with a strong correlation between them (r=0.792). Communication features did not significantly influence UX (β=0.053, p=0.196), challenging assumptions about virtual connectedness and indicating that communication design should better support social interaction. These findings highlight the importance of well-designed, interactive virtual spaces and suggest that developers and educational institutions prioritize environmental design to advance immersive learning and broader Metaverse applications.